Seven steps to separating difference from disability - Collier, Catherine. 4 0 16; 5 (Thousand Oaks, CA : Corwin, 2011)
Outlines a seven step process and examines case studies to help teachers adapt the Response to Intervention--RTI--model, identify the strengths and needs of students, and make decisions to improve student education.
Includes bibliographical references (p. 149-155) and index.
Professional;Professional.
Keywords: 2 -- 0; 6; Education;Diagnosis;Study and teaching;Foreign speakers. -- Linguistic minorities;Learning disabilities;English language -- United States.;United States.;United States -- 20; 20; 2